Performance of OCDMA systems with new spectral direct detection (SDD) technique using enhanced double weight (EDW) code - Mohamad Khazani, Abdullah; Hasoon, Feras N.; Syed Alwee Aljunid, Syed Junid; Sahbudin, Shaari (Elsevier B.V., 2009)
Link to publisher's homepage at www.elsevier.com